(3GdMOjK aj JGQjN dHfGf hGdHdGO GdYQHjIs (3ddUa GdKGdK GdKGfhj TgGOI GdKGfhjI GdYGeIs - (3MGhj(B, (3YHO GdMSjfs; (3eQhI(B, (3eGgQIs ((3HjQhJs (3OGQ HQcGJs, 2008)
(3cJGHkG hGajkG hcGajkG deGOI GdJGQjN ddSfI GdKGdKI GdKGfhjI MSH GdefgL GdQSej GdebQQ dLejY GdaQhY (B. (3Gf GdeYdheGJ eHSWI heNJUQI hMSH CSS GdJUMjM GdeJYHYI aj GdGeJMGfGJ GdQSej, ceG jTed GdcJGH HYV Uh GdTNUjGJ GdJGQjNjI GdHGQRI hGdNQGFW GdJGQjNjI hGdLZQGajI chSGFd JYdejI hHCSFdI gGeI aj fgGjI cd OQS(B. (3ceG jMJhj GdcJGH Ydi feGPL dCSFdI GdGeJMGfGJ GdQSejI GdhGQOI efP YGe (B2004 (3hMJi YGe (B2007.s
(3dHfGf NdGd GdMQH GdYGdejI GdChdi (B-- (3JMbjb GdGSJbdGd (B-- (3GdKhQI GdYQHjI (B-- (3GfgjGQ GdGeHQGWhQjI GdYKeGfjI (B-- (3aJM bfGI GdShjS (B-- (3GdKhQI GdLRGFQjI GdcHQi(B-- (3OhQGJ GdGeJMGfGJ GdQSejI hCSS JUMjMgGs
Keywords: (3JGQjNs